Mechanical bowel preparation before gynecologic laparoscopic procedures: Is it time to abandon this practice?. Issue 4 (8th February 2021) - Kathopoulis, Nikolaos; Chatzipapas, Ioannis; Valsamidis, Dimitrios; Samartzis, Konstantinos; Kipriotis, Konstantinos; Loutradis, Dimitrios; Protopapas, Athanasios
Abstract: Aim: To examine the influence of mechanical bowel preparation on surgical field visualization and patients' quality of life during benign gynecologic laparoscopic procedures. Methods: A single blind, randomized, controlled trial was undertaken with laparoscopic gynecologic surgical patients to one of the following three groups: liquid diet on the preoperative day; mechanical bowel preparation with oral polyethylene glycol (PEG) solution; minimal residue diet for 3 days. Primary outcomes included assessment of the condition of small and large bowel and the overall quality of the surgical field. Additional measures included assessment of patients' preoperative symptoms, tolerance of the preparation method and compliance to the protocol, postoperative symptoms and bowel function. Results: One hundred forty‐four patients were randomized as follows: 49 to liquid diet, 47 to mechanical bowel preparation, and 48 to minimal residue diet. Most characteristics were similar across groups. The intraoperative surgical view and the condition of large and small bowel were equal or inferior at the patients who received mechanical bowel preparation compared with the other groups. The 4‐point Likert scale scoring for small bowel (2.51 vs. 2.72 vs. 2.81, p = 0.04), large bowel (2.26 vs. 2.38 vs. 2.48, p = 0.32) and overall operative field quality (2.34 vs. 2.67 vs. 2.67, p = 0.03) demonstrated no advantage from the use of preoperative mechanical bowel preparation over liquid diet and minimal residue diet, respectively. Preoperative discomfort was significantly greater in the mechanical bowel preparation group. Conclusion: Mechanical bowel preparation before gynecologic laparoscopic operations for benign pathology could be safely abandoned. Clinical Trial Registration: ISRCTN registry, https://doi.org/10.1186/ISRCTN59502124 (No 59502124).